r-HuEPO treatment and serum total glutathione S-transferases activities - Kaptanoglu, Bunyamin; Dalmaz, Mahmut; Kosar, Ali; Yeksan, Mehdi; Akkus, Idris; Yeksan, Nurten; Alici, Suleyman (Annals of Medical Research, 2021)
None
Keywords: s : r-HuEPO, glutathione S-transferases